Photocatalytic degradation of ciprofloxacin by a novel Z-scheme CeO2–Ag/AgBr photocatalyst: Influencing factors, possible degradation pathways, and mechanism insight - Wen, Xiao-Ju; Niu, Cheng-Gang; Zhang, Lei; Liang, Chao; Guo, Hai; Zeng, Guang-Ming (Journal of catalysis, 2018)
A novel Z-scheme system of CeO2–Ag/AgBr heterostructure photocatalyst exhibits excellent ability to eliminate ciprofloxacin under visible light irradiation. [Display omitted] •Novel Z-scheme CeO2–Ag/AgBr photocatalysts were prepared.•Superior photocatalytic activity for the degradation of ciprofloxacin (CIP) refractory pollutants was obtained.•The factors affecting the photocatalytic performance were investigated.•A plausible degradation pathway for CIP was proposed.•A Z-scheme photocatalytic mechanism was proposed. In this study, CeO2–Ag/AgBr composite photocatalysts with a Z-scheme configuration were fabricated by in situ interspersal of AgBr on CeO2 and subsequent photoreduction process. The CeO2–Ag/AgBr composites exhibited enhanced photocatalytic activity for the photodegradation of ciprofloxacin (CIP) under visible light irradiation. The effects of initial CIP concentration and various inorganic salts were investigated in detail. Three-dimensional excitation–emission matrix fluorescence spectra were used to further monitor the CIP molecule degradation. Plausible degradation pathways for CIP were proposed based on LC-MS instruments. Photoluminescence, electrochemical impedance spectroscopy, and photocurrent tests indicated the rapid transfer and migration of electrons–holes can be achieved in this ternary photocatalytic system. The enhanced photocatalytic performances of CeO2–Ag/AgBr could be credited to the accelerated interfacial charge transfer process and the improved separation of the photogenerated electron–hole pairs. The existence of a small amount of metallic Ag is conducive to the formation of a stable Z-scheme photocatalytic system. This work would pave the route for the design of novel Z-scheme photocatalytic systems for application in solar-to-fuel conversion and photocatalytic water treatment.